2005
DOI: 10.1016/j.humpath.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protease-activated receptors 1 and 2 in melanocytic nevi and malignant melanoma

Abstract: Summary Protease-activated receptors (PARs) are members of the G protein-coupled receptor superfamily that are activated by the proteolytic cleavage of their amino terminal domain. PAR-1 activation by thrombin results in several biologic effects, including platelet adhesion to other cells or extracellular matrix, fibroblast, and endothelial cell growth, whereas PAR-2, activated by trypsin, has mainly a proinflammmatory and angiogenetic role. PAR-1 and PAR-2 modulate cell proliferation in physiopathologic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 37 publications
(41 reference statements)
2
72
0
1
Order By: Relevance
“…Several reports indicate that thrombin participates in melanoma growth and metastasis. 38 We have recently reported that thrombin receptor PAR-1 is unregulated in the initial phases of melanocytic tumor transformation and progression 39 and it has been shown that in cutaneous melanoma, loss of expression of the transcription factor activator protein-2a (AP-2), correlates with overexpression of PAR-1 and the acquisition of a malignant phenotype. 40 Thus, it may be proposed that thrombin participates in melanoma progression by different signaling pathways, including PAR-1 and Jagged-1 cleavage.…”
Section: Expression Of Notch Receptors and Their Ligands In Cutaneousmentioning
confidence: 99%
“…Several reports indicate that thrombin participates in melanoma growth and metastasis. 38 We have recently reported that thrombin receptor PAR-1 is unregulated in the initial phases of melanocytic tumor transformation and progression 39 and it has been shown that in cutaneous melanoma, loss of expression of the transcription factor activator protein-2a (AP-2), correlates with overexpression of PAR-1 and the acquisition of a malignant phenotype. 40 Thus, it may be proposed that thrombin participates in melanoma progression by different signaling pathways, including PAR-1 and Jagged-1 cleavage.…”
Section: Expression Of Notch Receptors and Their Ligands In Cutaneousmentioning
confidence: 99%
“…Thrombin binds PAR-1 and mediates increased invasiveness and metastatic potential of cancer cells [33][34][35] and enhanced cancer cell adhesion to platelets [36][37][38], endothelial cells [39], fibronectin and Von Willebrand factor [12,37]. Inhibition of thrombin by Hirudin may switch off PAR-1 signalling resulting in decreased tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we and others have shown that melanoma tumors have increased PAR-1 expression compared with nevi (5,6). Recently, we demonstrated that systemic delivery of PAR-1 siRNA encapsulated into neutral nanoliposomes inhibited tumor growth and experimental lung metastasis of melanoma cells in vivo (7).…”
mentioning
confidence: 83%